The Effectiveness of Husbands\' ‌Awareness of Menopausal Complications on Physical Psychological Experiences of Postmenopausal Women - Sedigheh Shariat Moghani; Mahdieh Ebrahimzadeh; Ali Safari; Jamshid Jamali (Guilan University of Medical Sciences, 2021)
‏Introduction: ‏ Women are subject to extensive changes during menopause.  ‏Life crises such as menopause can affect womenchr('39')s health and is a turning point in their lives.  ‏The husbands are the most important and closest people who can support their wives in this evolutionary crisis with their correct understanding of the situation. ‏Objective: ‏This study aimed to determine the effectiveness of husbandschr('39') ‏awareness of the physical and psychological experiences of postmenopausal women. Materials and Methods: ‏This randomized clinical trial study was performed on ‎150 ‏married postmenopausal women in Kashmar City, Iran, in ‎2019.  ‏The husbands of the intervention group received ‎three ‏sessions ‎(60 ‏minutes) ‏of the menopause training program with one-week intervals.  ‏The spouses of both groups received routine care at the health center.  ‏The questionnaire of psychological and physical experiences of postmenopausal women and measuring menchr('39')s awareness of menopause in both groups was completed before the intervention and one month after the intervention.  ‏The collected data were analyzed using descriptive statistics and inferential statistics of the Chi-square, ‏paired t test, ‏independent t test, and analysis of covariance. Results: ‏The mean ±SD age of women in the intervention group was ‎51.13 ±2.68 ‏years, and their mean ±SD menopausal age was ‎49.09 ±2.60 years.  ‏The mean ±SD score of menopausal experiences before the intervention was ‎144.99 ±38.09 ‏in the intervention group and ‎143.47 ±28.48 ‏in the control group and ‎105.53 (35.41) ‏in the intervention group, and ‎118.82 (82.21) ‏in the control group. ‏The statistical test showed that the mean score of menopausal experiences and the range of adaptation after the intervention and also between the two groups have statistically significant differences with each other (P ‎= 0.001). Conclusion: ‏Menopause has adverse physical and psychological symptoms.  ‏An intervention program to increase the awareness of men during menopause reduces negative menopausal experiences in women.